Facile synthesis of nitrogen-doped carbon dots from lignocellulosic waste - Issa, Mohammed Abdullah; Zainal Abidin, Zurina; Sobri, Shafreeza; Abdul Rashid, Suraya; Mahdi, Mohd Adzir; Ibrahim, Nor Azowa; Pudza, Musa Yahaya (MDPI, 2019)
The current research mainly focuses on transforming low-quality waste into value-added nanomaterials and investigating various ways of utilising them. The hydrothermal preparation of highly fluorescent N-doped carbon dots (N–CDs) was obtained from the carboxymethylcellulose (CMC) of oil palm empty fruit bunches and linear-structured polyethyleneimines (LPEI). Transmission electron microscopy (TEM) analysis showed that the obtained N–CDs had an average size of 3.4 nm. The N–CDs were monodispersed in aqueous solution and were strongly fluorescent under the irradiation of ultra-violet light. A detailed description of the morphology and shape was established using Fourier transform infrared (FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS). It was shown that LPEI were successfully tuned the fluorescence (PL) properties of CDs in both the intrinsic and surface electronic structures, and enhanced the quantum yield (QY) up to 44%. The obtained N–CDs exhibited remarkable PL stability, long lifetime and pH-dependence behaviour, with the excitation/emission maxima of 350/465.5 nm. Impressively, PL enhancement and blue-shifted emission could be seen with the dilution of the original N–CDs solution. The obtained N–CDs were further applied as fluorescent probe for the identification of Cu2+ in aqueous media. The mechanism could be attributed to the particularly high thermodynamic affinity of Cu2+ for the N-chelate groups over the surface of N–CDs and the fast metal-to-ligand binding kinetics. The linear relationship between the relative quenching rate and the concentration of Cu2+ were applied between 1–30 µM, with a detection limit of 0.93 µM. The fluorescent probe was successfully applied for the detection of Cu2+ in real water. Moreover, a solid-state film of N–CDs was prepared in the presence of poly (vinyl alcohol) (PVA) polymer and found to be stable even after 72-h of continuous irradiation to UV-lamp. In contrast to the aqueous N–CDs, the composite film showed only an excitation independent property, with enhanced PL QY of around 47%. Due to the strong and stable emission nature of N–CDs in both aqueous and solid conditions, the obtained N–CDs are ideal for reducing the overall preparation costs and applying them for various biological and environmental applications in the future.